Sex-related differences in oxygen consumption recovery after high-intensity rowing exercise during childhood and adolescence - Bardin, J.; Maciejewski, H.; Diry, A.; Thomas, C.; Ratel, S. (Pediatric Exercise Science, 2022)
Purpose: To determine sex-related differences in oxygen consumption (VO2) recovery after high-intensity exercise during childhood and adolescence. Methods: Forty-two boys and 35 girls (10-17 y) performed a 60-second all-out test on a rowing ergometer. Postexercise (VO2) recovery was analyzed from (1) the (VO2) recovery time constant obtained from a biexponential model (t1 (VO2) ) and (2) excess postexercise oxygen consumption calculated over a period of 8 minutes (EPOC8) and until t1 (VO2) was reached (EPOCt1). Multiplicative allometric modeling was used to assess the concurrent effects of body mass or lean body mass, and age on EPOC8 and EPOCt1. Results: EPOC8 increased significantly more in boys from the age of 14 years. However, the sex difference was no longer significant when EPOC8 was analyzed using an allometric model including body mass + age or lean body mass + age. In addition, despite a greater increase in EPOCt1 in boys from the age of 14 years, t1 (VO2) was not significantly different between sexes whatever age. Conclusion: While age and lean body mass accounted for the sex-related differences of EPOC during childhood and adolescence, no significant effect of age and sex was observed on the (VO2) recovery time constant after high-intensity exercise.